2019
DOI: 10.1007/s40801-019-0158-0
|View full text |Cite
|
Sign up to set email alerts
|

PEARL: A Non-interventional Study of Real-World Alirocumab Use in German Clinical Practice

Abstract: Background Several lipid guidelines recommend that proprotein convertase subtilisin/kexin type 9 inhibitors should be considered for patients with atherosclerotic cardiovascular disease who are inadequately treated with maximally tolerated lipid-lowering treatment. Objectives The PEARL study assessed the efficacy and safety of the proprotein convertase subtilisin/kexin type 9 inhibitor alirocumab in patients with hypercholesterolemia in a real-world setting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
(37 reference statements)
3
11
0
1
Order By: Relevance
“…This relatively high number of statin-intolerant patients is due to enrolled patients were being treated at a lipid clinic that specializes in the treatment of statin-intolerant patients. A similar ratio of statin-intolerant patients was observed in the German PEARL real-world study [ 38 ]. Patients without statin therapy demonstrated significantly lower reductions in LDL-C from baseline to week 4 than did patients on background statins (53.1% and 60.2%, respectively; P < 0.0001).…”
Section: Discussionsupporting
confidence: 81%
“…This relatively high number of statin-intolerant patients is due to enrolled patients were being treated at a lipid clinic that specializes in the treatment of statin-intolerant patients. A similar ratio of statin-intolerant patients was observed in the German PEARL real-world study [ 38 ]. Patients without statin therapy demonstrated significantly lower reductions in LDL-C from baseline to week 4 than did patients on background statins (53.1% and 60.2%, respectively; P < 0.0001).…”
Section: Discussionsupporting
confidence: 81%
“…A recent study on effectiveness and safety in a real-life setting in Germany largely confirmed findings from the ODYSSEY study program 11 . As real-world data are still sparse, the current observational study was conducted to estimate the effectiveness and safety of alirocumab in an Austrian population.…”
Section: Introductionsupporting
confidence: 54%
“…Based on the inclusion criteria that stipulated patients to be on treatment with alirocumab, it could be expected that the majority of patients had a total or partial statin intolerance. The design of this study was concordant with a prior noninterventional study (PEARL) conducted in Germany in 619 patients 11 . A crucial difference to the real-world data in Germany is that patients were recruited from different specialists: in Austria, prescribing physicians were endocrinologists and were based in a hospital setting (according to the Austrian reimbursement regulation).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Therapeutic approaches to lower LDL-C other than statins therefore play an important role in clinical practice. Real-world data from Germany underline the importance of antibodies against PCSK9 in this setting by showing that among patients treated with alirocumab, 73% had partial or total statin intolerance ( Parhofer et al, 2019 ).…”
Section: Ldl-c Lowering With Pcsk9 Antibodiesmentioning
confidence: 99%